Inferiority complex in women's oppression on Medea & The Glass Menagerie - Hartanto, Bayu; Kusuma, Dwi Linda; Lililacs , Admin (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2022)
The purpose of this study is to analyze the inferiority complex of women characters from various eras based on their stories. This study uses the id, ego, superego, and defense mechanism by Freud and inferiority complex by Heidbreder. Through the descriptive analytical method, this analyze is to help the interpretation of the women characters state of minds including their stress coping mechanism and classify their types of inferior complex. The results of this study shows that Medea had a high tendency to feel insecure as a result of her husband’s betrayal, and she mostly used projection as a defense mechanism to revenge her husband. Meanwhile, Amanda demonstrates the use of identification as a stress escapement from societal pressure, as well as her inferiority complex when faced with a guy caller. Due to the stress of high expectations in attracting gentleman caller, Laura mostly used rationalization as a defense mechanism.